The utilization of weather and climate information to support marine and fisheries activities - Yopi Ilhamsyah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2013)
Abstract. Weather and climate condition are certainly changing. In addition to an early warning of the atmospheric hazard, update information about the current and future status of atmospheric condition is necessary to support public activities. The purpose of this paper is to provide freely online weather and climate information that can be easily accessed by the community. The weather and climate products from an official Indonesian agency for Meteorology, Climatology, and Geophysics are used in this paper. The agency serves informative and public accessible weather and climate products. In addition, products from foreign public or private meteorological services are also used since they offer valuable spatial and temporal information including early warning of atmospheric hazards that benefit to assist local community in their daily activities. In marine and fisheries sector, it helps to minimize the risk and losses that may be arisen due to the changing of atmospheric condition, so that, the productivity in this sector is expected to increase in the future Keywords: Atmospheric condition; Weather and climate products; Marine and fisheries Abstrak. Kondisi cuaca dan iklim mengalami perubahan dengan pasti. Selain sebagai peringatan dini tentang bahaya atmosfer, informasi mengenai status terkini dan mendatang mengenai kondisi atmosfer adalah penting guna mendukung aktifitas masyarakat. Tujuan dari makalah ini adalah untuk menyajikan informasi pelayanan cuaca dan iklim secara gratis dan online yang dapat dengan mudah diakses oleh masyarakat. Makalah ini menggunakan produk cuaca dan iklim dari Badan Meteorologi, Klimatologi dan Geofisika Indonesia. Badan ini melayani produk yang informatif dan mudah diakses oleh masyarakat. Selain itu, produk-produk dari layanan meteorologi asing baik milik pemerintah atau swasta juga digunakan dalam makalah ini karena menyediakan informasi spasial dan temporal yang berharga termasuk peringatan dini yang berguna untuk membantu masyarakat lokal dalam melaksanakan kegiatan sehari-hari. Dalam sektor kelautan dan perikanan, informasi ini membantu untuk mengurangi resiko dan kerugian yang mungkin terjadi akibat perubahan kondisi atmosfer, sehingga produktifitas pada sektor ini diharapkan dapat meningkat di masa mendatang. Kata kunci: Kondisi atmosfer; Produk cuaca dan iklim; Kelautan dan perikanan